The Efficiency of Integrating Strategy Between Generative Learning and Concept Maps in Developing Grammatical Skills Among Third-grade Intermediate Female Students in Taif Governorate - Alotaibi, Engud obaid nawar (Journal of Educational and Psychological Sciences, 2020)
The research aimed to reveal the efficiency of using a strategy based on the integration between generative learning and concept maps in the development of grammatical skills. The semi-experimental approach was used, two tools were designed: a list of grammatical skills, and a grammatical skills test; to reveal the efficiency of a strategy based on the integration between generative learning and concept maps in the development of grammatical skills among third-grade intermediate class, two research materials were designed: the teacher’s and female student guides; to develop grammatical skills, after the researcher verified the validity and reliability of the study tools, she began applying them to the study sample consisting of (58) students in the third grade intermediate; distributed in two groups; (29) experimental, and (29) control, after performing the necessary statistical analyses, the study showed that there is a statistically significant difference at the significance level (0.05) between the average scores of female students of the experimental and control groups in the post-application of the grammar skills test; at the macro level, the experimental got a total average (26.34 for the experimental), while the control got a total average (16.79 for the control) at the level of understanding and grammatical interpretation - grammatical classification - grammatical deduction - grammatical application - grammatical rule - in its overall score in favor of the experimental group. On the focus of the study results, the study recommended the necessity of curriculum planners' interest in developing grammar teaching by employing modern strategies such as generative learning and concept maps, conducting training courses for Arabic language teachers to help them in use of modern strategies. The study also recommended to motivate grammar teachers and third intermediate female students to adhere both writing and oral grammatical skills.
Keywords: Efficiency; Strategy; Integration Between Generative Learning and Concept Maps; Grammatical Skills Development; Third Intermediate Female Students